Desain Dan Simulasi Suspensi Sepeda Motor Dengan Solidwork 2012 - Khairul Umurani Khairul Umurani; Taufik Amri (Fakultas Teknik UMSU, 2018)
Motorcycle is one of the means of transportation that is widely used today. The comfort and stability of a motorcycle is determined by the design of the suspension system used in the vehicle. On a motorcycle the suspension system consists of the front and rear suspension which has the same function, which is to reduce vibration due to road field irregularities. In the rear suspension there are two types of suspension systems, this suspension includes double suspension and single suspension or commonly called monoshock. The monoshock suspension system has one spring and one damper in the middle of the Swing Arm and is directly connected to the vehicle body. This suspension system is mostly found on motorbikes with large cc, because the work of the motorcycle suspension system is quite heavy. In the design process of the monoshock suspension system using 2012 solidwork. By using the 2012 solidwork suspension system a suspension design and simulation of the coil spring with several variations of Pitch and Revolution were made to obtain stress, displacement, and strain results with a predetermined load of 1200N. The results of the monoshock suspension simulation are coil springs with Pitch and Revolution, where the lower part of the coil is spongy and the top of the joint has the appropriate stress, displacement and strain values.